An Analysis of Teachers’ Beliefs and Practices in Vocabulary Teaching at Junior High Schools Gunuang Omeh - Metria Dicky Putra; Nofrina Eka Putri (Journal of English Language Teaching, 2023)
This research aimed to analyze of teacher beliefs and practices in vocabulary teaching at Junior High Schools Gunuang Omeh. This research used Graves theory with which teachers’ beliefs and practices in teaching vocabulary are seen, including, providing rich and varied language experiences, teaching individual words explicitly, teaching word-learning strategies, and fostering word consciousness. This research employed qualitative approach. The participants of this study were four English teachers. The instruments of this research were interviews and observations. The result of this research shows that teachers generally hold similar beliefs in four of indicators, except in one aspect. One teacher believes that teachers should teach definition of new words directly to students while others prefer to teach them implicitly. The research also found that in certain aspect, teachers’ beliefs and practices are not aligned. Only two teachers taught vocabulary used various kinds of game. The researcher suggest that teacher should improve the quality of theirs by using games to teach vocabulary. This research can be addition reference for the same field.